Upaya Peningkatan Kemampuan Sumber Daya Manusia Dalam Menunjang Efektivitas Kerja Pegawai (Studi Pada Dinas Pendidikan, Kepemudaan dan Olah Raga Kota Kendari) - Pertiwi, Ajeng; Tawai, Adrian; Aminuddin, Aminuddin (REZ PUBLICA, 2021)
The purpose of this study was to determine the efforts to increase human resource capacity in supporting the effectiveness of employees at the Kendari City Education, Youth and Sports Office. As for the dimensions of efforts to increase human resource capabilities, as seen from; a) education, b) training, and c) courses. While the dimensions of work effectiveness, as seen from; a) punctuality, b) application of discipline, c) accuracy of employees, and d) achievement of targets. The results of this study indicate that; efforts to increase the capacity of Human Resources at the Kendari City Education, Youth and Sports Office have been carried out quite well in supporting the work effectiveness of employees. The work effectiveness of employees at the Kendari City Education, Youth and Sports Office has been going quite well. This can be seen in the responses of respondents starting from the dimensions of employee discipline in completing work on time and implementing employee work discipline, employee accuracy in completing office tasks, and achieving targets against predetermined targets.